Fundamentals of statistics - Amid, Diego M. (Quezon City, Philippines : Lorimar Publishing Company Inc., 2005)
The goal of this text is to present statistics in a clear and interesting way. The explanation of statistical methods and concepts is clear and concise. Moreover the style is more user-friendly and easy to understand.
Chapter 1. Introduction -- Chapter 2. frequency Distribution -- Chapter 3. Measures of central tendency -- Chapter 4. Measures of Dispersion -- Chapter 5. Probability -- Chapter 6. Probability distributions -- Chapter 7. Linear correlation -- Chapter 8. Inferential statistics.
Includes bibliographical references.
Keywords: BUSINESS -- STATISTICS